x2-12x-45=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -45 and whose sum is -12.

-15,3

Write the factored form using these integers.

(x-15)(x+3)=0

(x-15)(x+3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-15=0

x+3=0

Set the first factor equal to 0.

x-15=0

Add 15 to both sides of the equation.

x=15

x=15

Set the next factor equal to 0.

x+3=0

Subtract 3 from both sides of the equation.

x=-3

x=-3

The final solution is all the values that make (x-15)(x+3)=0 true.

x=15,-3

Solve Using the Square Root Property x^2-12x-45=0